2022
DOI: 10.5194/essd-14-3423-2022
|View full text |Cite
|
Sign up to set email alerts
|

Observational data from uncrewed systems over Southern Great Plains

Abstract: Abstract. Uncrewed Systems (UxS), including uncrewed aerial systems (UAS) and tethered balloon/kite systems (TBS), are significantly expanding observational capabilities in atmospheric science. Rapid adaptation of these platforms and the advancement of miniaturized instruments have resulted in an expanding number of datasets captured under various environmental conditions by the Department of Energy (DOE) Atmospheric Radiation Measurement (ARM) user facility. In 2021, observational data collected using ARM UxS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…The POPS is a lightweight (550 g) optical particle counter measuring particle number and particle size distribution in the range of 115 nm -3.37 µm at a 1-second time resolution. POPS was designed to be used on mobile platforms and has already been deployed with success on radiosonde balloons (Yu et al, 2017(Yu et al, , 2019Kloss et al, 2020), tethered balloons (de Boer et al, 2018;Creamean et al, 2021;Pilz et al, 2022;Mei et al, 2022;Walter et al, 2023;Lata et al, 2023), fixed-wing UAVs (Telg et al, 2017;Kezoudi et al, 2021;Mei et al, 2022;DeFelice et al, 2023), and other multirotor UAVs (Liu et al, 2021;Brus et al, 2021).…”
Section: Measurement Uavmentioning
confidence: 99%
See 2 more Smart Citations
“…The POPS is a lightweight (550 g) optical particle counter measuring particle number and particle size distribution in the range of 115 nm -3.37 µm at a 1-second time resolution. POPS was designed to be used on mobile platforms and has already been deployed with success on radiosonde balloons (Yu et al, 2017(Yu et al, , 2019Kloss et al, 2020), tethered balloons (de Boer et al, 2018;Creamean et al, 2021;Pilz et al, 2022;Mei et al, 2022;Walter et al, 2023;Lata et al, 2023), fixed-wing UAVs (Telg et al, 2017;Kezoudi et al, 2021;Mei et al, 2022;DeFelice et al, 2023), and other multirotor UAVs (Liu et al, 2021;Brus et al, 2021).…”
Section: Measurement Uavmentioning
confidence: 99%
“…The POPS has been extensively described, characterized, and validated in previous studies (Gao et al, 2016;Mei et al, 2020;Liu et al, 2021;Mei et al, 2022;Kasparoglu et al, 2022;Pilz et al, 2022;Mynard et al, 2023). Here, we performed selected tests in the laboratory to ensure that POPS UAV and POPS TBS count and size particles correctly, detailed in Appendix A.…”
Section: Validation Of Pops Measurements On the Measurement Uavmentioning
confidence: 99%
See 1 more Smart Citation
“…While the ArcticShark was undergoing upgrades and modifications in 2021, the AAF staff collaborated with the Mississippi State University (MSU) Raspet Flight Research Laboratory (RFRL) to fly the ArcticShark scientific payload on an RFRL TS-B3-XP TigerShark. A description of all the datasets obtained from the AAF payload can be found here [32]. A comparison between the TigerShark XP and ArcticShark is shown in Table 1.…”
Section: Mid-size Uas Descriptionmentioning
confidence: 99%
“…We believe that this is due to the thickness of the window on the thermal imager lens. Notably, Mei et al found that the Apogee IRT surface temperature readings varied with altitude, likely resulting from changing internal temperature [32]. The spectral profile was collected at different altitudes to test for the effects of atmospheric scattering.…”
Section: Thermal Imagery Comparison To Infrared Thermometersmentioning
confidence: 99%